Cadbury India – Sweet Turning Sour - Fernandes, Semila F; Gupta, Pooja; Vidyasagar, A (Ushus Journal of Business Management, 2021)
Mondelez global CEO Irene Rosenfeld has been concerned over slow growth in India unit. Since 2015, she has expressed her concern over this slow growth rate. “India is a market that we’re watching closely....... It’s just growing at a slower rate than it had been. So I want to be very clear; it’s just we’d like to see it get back up to the high single-digit, double-digit rates that it had been growing at since we acquired the Cadbury business."1Rosenfeld had said at an investors call in August last year.2Mondelez India, which acquired Cadbury India in 2012, wasseeking to boost growth, which had fallen to single digits in the first half of 2015.